2009
DOI: 10.1016/j.fertnstert.2008.01.075
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal instability in rhesus macaque preimplantation embryos

Abstract: Objective-To establish a relevant animal model to systematically investigate chromosomal instability in human oocytes and preimplantation embryos. Design-Prospective rhesus monkey IVF study.Setting-Academic laboratory, Oregon National Primate Research Center and Caribbean Primate Research Center. Patients-Young Rhesus macaque females.Interventions-In vitro produced (IVP) entire rhesus macaque preimplantation embryos were cytogenetically assessed using a 5-color fluorescent in situ hybridization (FISH) assay de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 47 publications
(64 reference statements)
1
25
0
Order By: Relevance
“…Rhesus chromosomes 6 and 12 were shown to be under expressed in our experiments (Figure 3B). These results are in agreement with previous published results showing chromosomal instability in rhesus preimplantation embryos [36, 37]. When global gene expression patterns were characterized, we found that the nhpESC gene expression was closer to skin fibroblasts rather than to the teratoma fibroblasts, although genetically they share their genome with teratoma fibroblasts and only half with skin fibroblasts.…”
Section: Resultssupporting
confidence: 93%
“…Rhesus chromosomes 6 and 12 were shown to be under expressed in our experiments (Figure 3B). These results are in agreement with previous published results showing chromosomal instability in rhesus preimplantation embryos [36, 37]. When global gene expression patterns were characterized, we found that the nhpESC gene expression was closer to skin fibroblasts rather than to the teratoma fibroblasts, although genetically they share their genome with teratoma fibroblasts and only half with skin fibroblasts.…”
Section: Resultssupporting
confidence: 93%
“…Ovarian stimulation was carried out as previously described [26]. In brief, rhesus macaques received a sequential regimen of recombinant human gonadotropins to support follicular growth.…”
Section: Methodsmentioning
confidence: 99%
“…Ovarian follicular growth in female rhesus macaques (age range between 4 and 13 years old) was supported using sequential administrations of recombinant human follicle stimulating hormone (rhFSH, Organon, Oss, The Netherlands) and recombinant human luteinizing hormone (rhLH, EMD Serono, Rockland, MA, USA) (18, 19). On the final day of the rhFSH administration, a single dose of recombinant human chorionic gonadotropin (rhCG; 750–1000 IU, i.m.)…”
Section: Methodsmentioning
confidence: 99%
“…The procedures for oocyte recovery, sperm collection, insemination and embryo culture have been described previously (1825). Fluid from ovarian follicles was aspirated 33 to 36 hours after the rhCG administration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation